Challenges of introducing new software for account opening: a case study on Mutual Trust Bank Ltd. - Saha, Anuradha (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.